Crossing the boundary between humans and animals: the extinct fox Dusicyon avus from a hunter-gatherer mortuary context in Patagonia (Argentina) - Prates, Luciano Raúl (2014)
The discovery of a grave of the late second millennium BC containing an extinct South American fox, Dusicyon avus, at Loma de los Muertos raises intriguing questions about the relationship between wild canids and humans. This sub-adult individual appears to have been buried in a human mortuary context in a comparable manner to adjacent human burials. It may have been kept as a pet and been considered part of the human social group. The ability of pets, especially canids, to leave the animal world and enter into a special relationship with people may be related to the cosmology of South American hunter-gatherers.